Corrosion activation by ammonium fluoride enhances the separation of chrysocolla and quartz by sulfidation flotation. (November 2022) - Zuo, Qi; Wu, Dandan; Cao, Jing; Wang, Ziang; Wen, Shuming; Huang, Lingyun; Chen, Huiqin
Graphical abstract: Highlights: A corrosion activation reagent of chrysocolla was proposed. The NH4 F had a satisfactory sulfidation flotation separation of chrysocolla and quartz. F – ions weakened the strength of the silicon-oxygen-aluminium bonds, and increased the active sites on the chrysocolla surface. NH4 F was used as surfactants to change the hydrophobicity of chrysocolla. Abstract: In this study, the effects of ammonium fluoride (NH4 F) on chrysocolla corrosion activation were investigated. Fluoride ions corroded the surface of chrysocolla and exposed more active copper particles to facilitate the catalytic sulfidation of ammonium, which increased the flotation recovery by 59.14 %. After treatment with a solution of NH4 F and Na2 S·9H2 O, atomic force microscopy (AFM) imaging revealed that the surface of chrysocolla was rougher than that treated with the Na2 S·9H2 O solution. This indicated that the F ions reacted with Al and Si ions on the mineral surface and corroded the mineral surface, and NH3 reacted with Cu ions to form Cu(NH3 )i 2+ (i = 1, 2, 3, 4) on the mineral surface and became adsorbed to the mineral surface. Time-of-flight secondary-ion mass spectrometry (ToF-SIMS) surface analysis and X-ray photoelectron spectroscopy (XPS) analysis revealed that the −Al−O−Si− structure of the chrysocolla surface was greatly damaged by NH4 F, and the formed Cu(NH3 ) + promoted the formation of CuS2 films through catalytic sulfidation to obtain chrysocolla with surface hydrophobicity. Fourier transform infrared (FTIR) spectroscopy analysis and adsorption capacity measurements showed that xanthate has strong adsorption capacity on the activated hydrophobic surface of chrysocolla. All the results showed that NH4 F contributes to the formation of more hydrophobic CuS2 films on the chrysocolla surface. The treatment with NH4 F resulted in a satisfactory separation of chrysocolla and quartz by sulfidation flotation.